Diversity of birds in Tranum Forest reserve, Pahang - Tuan Marina T.I, Forestry Department Peninsular Malaysia (FDPM), Jalan Sultan Salahuddin, Kuala Lumpur (Malaysia). Section of Forest Economy (Jabatan Perhutanan Semenanjung Malaysia, 2013)
A total of 830 observations of birds were recorded at Fraser`s Hill belonging to 111 species. The most dominant species observed during the survey was Pycnonotus melanicterus. The insectivore feeding guild has the highest diversity (H`= 2.68) compared to the frugivores feeding guild (H` = 1.79). The density estimates for the total number of birds detected at Fraser`s Hill was considered relatively high with 193,950 individuals (71.8 individuals per ha)· The location of this forest that extended to Fraser`s Hill may influence the species diversity in the area and it is expected to have more species recorded.